Structural Effect of Polyimide Precursors on Highly Thermally Conductive Graphite Films - Jin, Jeong-Un; Hahn, Jae Ryang; You, Nam-Ho (ACS Publications, 2022)
In this study, polyimide (PI) with high carbonization yield was used as a precursor to prepare graphite films with high thermal conductivity. The crystallinity, grain size, and thermal conductivity of the graphite films were characterized and found to vary according to the chemical structure of the PI precursor. Aromatic PIs containing ortho-substituted hydroxyl groups in the PI main chain (DHB-BPDA) were synthesized by the polycondensation reaction of 3,3'-dihydroxybenzidine (DHB) and 3,3',4,4'- biphenyltetracarboxylic dianhydride (BPDA). The DHB-BPDA is converted to a polybenzoxazole (PBO) structure through thermolysis reaction during carbonization. The PBO containing a benzene ring and a heterocycle group can provide a strong main chain and high thermal stability due to its resonant structure. The graphite film prepared from DHB-BPDA exhibited a large grain size (63.727 nm) and a high thermal conductivity of 916 W/(mK).